2010
DOI: 10.1161/circresaha.109.216291
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: The Cardiac Myosin Binding Protein C Arg502Trp Mutation

Abstract: MethodsStandard methods for DNA isolation and analyses were used and are described in the expanded Methods section, available in the Online Data Supplement at http://circres.ahajournals.org. ResultsThirty-four of 1414 (2.4%) consecutive unrelated HCM probands who underwent genetic testing (Supplement Methods), harbored the MYBPC3 Arg502Trp variant. MYBPC3 residue 502 has been highly conserved during evolution (Online Figure I). Insertion of tryptophan at position 502 substitutes a nonpolar hydrophobic residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 16 publications
(25 reference statements)
2
56
0
Order By: Relevance
“…In addition, Iceland's remote, rugged terrain and harsh environment may have produced negative effects on deleterious HCM mutations and may have contributed to the lower population prevalence of HCM in Iceland (1:1600) compared with the United States (1:500). 7 The founder mutation in the Icelandic population, similar to previously described founding mutations in Finland, 29 the Netherlands, 30 India, 31,32 Japan, 33 South Africa, 24 Spain, 34 France, 35 and the United States, 36 affects the MYBPC3 gene. Unlike deleterious HCM mutations, founder MYBPC3 mutations have a minimal effect on overall survival, particularly during the reproductive years of life.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, Iceland's remote, rugged terrain and harsh environment may have produced negative effects on deleterious HCM mutations and may have contributed to the lower population prevalence of HCM in Iceland (1:1600) compared with the United States (1:500). 7 The founder mutation in the Icelandic population, similar to previously described founding mutations in Finland, 29 the Netherlands, 30 India, 31,32 Japan, 33 South Africa, 24 Spain, 34 France, 35 and the United States, 36 affects the MYBPC3 gene. Unlike deleterious HCM mutations, founder MYBPC3 mutations have a minimal effect on overall survival, particularly during the reproductive years of life.…”
Section: Discussionsupporting
confidence: 72%
“…Although initial studies supported the notion of mutation-specific clinical outcomes, 25 subsequent studies 26 and the identification of the vast clinical and genetic heterogeneity in HCM have limited the clinical utility of genotype in guiding management. 1,27 In the current study, MYH7 mutation carriers were found to be significantly younger, and they presented at a younger age, as compared with MYBPC3 mutation carriers. Mutations in specific genes did not correlate significantly with clinical features, but the number of gene mutations correlated with some measures of disease severity, specifically the occurrence of an OHCA or SCD in the proband.…”
Section: Discussionsupporting
confidence: 42%
“…In these adult cases, a more severe HCM phenotype is generally seen, characterized by an earlier age of onset around the second decade or during childhood (Table 2). 6,14,15,[20][21][22][23][24][25][26][27][28][29][30] In a recent study on sarcomeric protein gene variants in childhood-onset HCM, 6 out of 84 children (7%) had compound variants. 6 This suggests that a gene-dosage effect might be responsible for manifestations at a younger age.…”
Section: Discussionmentioning
confidence: 99%